Designing a suggested educational training field to develop a number of physical abilities as an extra-curricular activity directed at middle school students (Journal of the College of Basic Education, 2022)
The countries of the world place great hopes on their education systems because one of their most important goals is the development of various aspects of life, by providing and preparing qualified and trained human resources that can do everything they need, as education, with its human and material dimensions, is the key to development whose goal and means are the human being, and The world has recently witnessed scientific progress in all fields, including the mathematical field, and this was not a coincidence, but rather by relying on other different sciences and their relevance in the mathematical field through the adoption of scientific research and studies as a basis for this development, which called on teachers to follow modern scientific methods and methods to reach To a comprehensive educational process in laying the foundations and scientific rules.